Linguistic creativity in Thai English fiction / Pairote Bennui - Bennui, Pairote (2013)
English in Thailand has not been yet accepted as another non-native variety because of the debatable notion of ‘Thai English’. The native variety of English is still considered the correct English in most domains in the Thai society. In the literary domain, the development of an English peculiar to the country can however be observed. This study thus examines features of linguistic creativity, namely lexis and discourse, in five contemporary English writings by Thai authors in order to identify indicators for a Thai variety of English. The selected collections of short stories are ‘Dragon’s Fin Soup: Eight Modern Siamese Fables’ (2002) by S.P. Somtow, ‘Sightseeing’ (2005) by Rattawut Lapcharoensap, and ‘The Umbrella and Other Stories’ (1998) by Supasiri Supunpaysaj while the novels are ‘Shadowed Country’ (2004) by Pira Canning Sudham and ‘Chalida’ (2002) by Salisa Pinkayan. The features are interpreted using an integrated approach which combines the World Englishes frameworks of Kachru (1983a; 1983b; 1985; 1986; 1987; 1992a; 1992b; 1995; and 2003), Strevens (1980; 1982; and 1987b), and Schneider (2007). Through textual analysis, findings reveal that the Thai writers highlight their English fiction with distinctive strategies of linguistic innovation. Morphologically, they create lexical borrowing, modes of address and reference, loan translation, coinages, semantic shifts, hybridisation, reduplication, acronyms, clipping, and ellipsis. Stylistically, they invent nativisation of context, nativisation of rhetorical strategies, nativisation of mantra, code-mixing and code-switching, the colloquial variety of English, and discourse styles. It appears that these characteristics are not only similar to those used by other non-Anglo English writers but also provide unique indicators for Thai English lexicon and discourse patterns. They are persisting features of the English development, contextualisation, innovation, nativisation, transcultural creativity, localisation, Thai cultural loading of English language, Thai identity construction of English literary discourse, realisation of thought patterns in Thai writing style, multilingual code repertoire in literary and cultural contact, structural similarities to New Englishes, structural uniqueness of Southeast Asian Englishes, and structural uniqueness of Thai English. There is evidence that ‘Thai English’ may be emerging as ‘a developing non-native variety’ in the Expanding Circle rather than ‘an established variety’ in the Outer Circle.